Electro‐ and Photocatalytic Generation of H2 Using a Distinctive CoII "PN3P" Pincer Supported Complex with Water or Saturated Saline as a Hydrogen Source. Issue 66 (7th November 2017) - Rao, Gyandshwar Kumar; Pell, Wendy; Gabidullin, Bulat; Korobkov, Ilia; Richeson, Darrin
Abstract: Efficient electrocatalytic production of H2 from mixed water/acetonitrile solutions was achieved using three new Co II complexes supported by the neutral pincer ligand bis(diphenylphosphino)‐2, 6‐di(methylamino)pyridine ("PN3 P"). At −1.9 V vs. Fc/Fc +, these catalysts showed 96 % Faradaic efficiency with added water or saturated aqueous saline at rates of up to 316 L(mol cat) −1 (cm 2 ) −1 h −1 using a glassy carbon working electrode. The complex [Co(κ 3 ‐2, 6‐Ph2 PNMe2 (NC5 H3 )Br2 ] (1 ) was also able to photocatalytically reduce water to hydrogen in the presence of a Ru(bpy)3 2+ photosensitizer and a reductant. Abstract : The new Co II pincer complex, [Co(κ 3 ‐2, 6‐Ph2 PNMe2 (NC5 H3 )Br2 ], is one of three reported complexes capable of both electrocatalytic and, in the presence of a photosensitizer, photocatalytic H2 production using water or saturated saline as the source.